Assessing learning and development through transdisciplinary problem-based invention education offerings - Couch, Stephanie; Paul, Kelli M.; Sullivan, Michelle; Sultana, Sabiha (Frontiers in Education, 2024)
Invention Education (IvE), a form of problem-based learning, presents new challenges for educational assessments in public schooling because traditional assessments were designed to evaluate learning in singular disciplines. This study explores the challenges and possibilities for assessing new knowledge and capabilities acquired through students’ engagement with multiple disciplines through IvE. Guided by constructivist and sociocultural theories, as well as an understanding of IvE principles and practices derived from the literature on IvE, we examine the phases of work within a national IvE program for high school students and educators. We then examine ways existing assessments align with the work at each stage of the IvE process. Findings from this case study underscore the need for a flexible assessment system with multiple measures (e.g., disciplinary knowledge and practices, skill inventories, etc.). The system must account for variations in learning contexts, individual and collective achievements, and varying lengths of time students engage in IvE.